Protein-energy malnutrition as a consequence of the hospitalization of gastroenterologic patients - Papini-Berto, Silvia Justina [UNESP]; Dichi, Jane Bandeira [UNESP]; Dichi, Isaias [UNESP]; Victória, Carlos Roberto [UNESP]; Burini, Roberto Carlos [UNESP] (My University, 1997)
The effects of the clinical and dietetics in patient managements on the protein-energy status of hospitalized patients were retrospectively (four yr) investigated in 243 adult (49 +/- 16 yr), male (168) and female (75) patients suffering from chronic liver diseases (42%), intestinal diseases with diarrhea (14%), digestive cancers (11%), chronic pancreatitis (10%), stomach and duodenum diseases (7%), acute pancreatitis (7%), primary protein-energy malnutrition (3%), esophagus diseases (3%), intestinal diseases with constipation 14 (2%) and chronic alcoholism (2%). The protein-energy nutritional status assessed by combinations of anthropometric and blood parameters showed 75% of protein energy malnutrition at the hospital entry mostly (4/5) in severe and moderate grades. The overall average of hospitalization was 20 +/- 15 days being the shortest (13 +/- 5,7 days) for esophagus diseases and the longest (28 +/- 21 days) for the intestinal diseases with diarrhea patients which also received mostly (42%) of the enteral and/or parenteral feedings followed by acute pacreatitis (41%) and digestive cancers (31%) patients. When compared to the entry the protein-energy malnutrition rate at the discharge decreased only 5% despite the increasing of 30% found on the protein-energy intake. The main improvement of the protein-energy nutritional status were attained to those patients showing protein-energy malnutrition milder degrees at the entry which belonged mostly to primary protein-energy malnutrition, acute pancreatitis and intestinal diseases with diarrhea diseases. The later two groups showed protein-energy nutritional status improvement only after the second week of hospitalization. The digestive cancers patients had their protein-energy nutritional status worsened throughout the hospitalization whereas it happened only in the first week for the intestinal diseases with diarrhea and chronic liver diseases patients, improving thereafter up to the discharge. The protein-energy nutritional status improvement found in few patients could be attributed to some complementary factors such as theirs mild degree of protein-energy malnutrition at entry and/or non-invasive propedeutics and/or enteral-parenteral feddings and/or longer hospitalization staying. The institutional causes for the unexpected lack of nutritional responses by the patients were probably the high demand for the few available beds which favour the hospitalization of the most severed patients and the university-teaching pressure for the high rotation of the available beds. Both often resulting in early discharging. In persisting the current physical area and attendance demand one could suggest an aggressive support early at the entry preceding and/or accompanying the more invasive propedeutical procedures.